Influence of Different Exercise Types on Health-Related Quality-of-Life in Men With Depressive Disorder in South Korea - Kim, Kyungjin; Koo, Kyo-Man (Frontiers in Public Health, 2022)
The purpose of this study was to investigate the influence of different exercise types (e.g., flexibility exercise, strength exercise, walking) on health-related quality of life (QOL) in men with depressive disorder in South (S) Korea. The data of 385 men aged 19 or older with depressive disorder were collected in S. Korea. KNHANES and EQ-5D index questionnaires were used to determine the purpose of this study. In addition, the complex sampling model was used to investigate the influence of different exercise types on health-related QOL in men with depressive disorder in S. Korea. In the outcomes, strength exercise and walking had significant influence on health-related QOL in men with depressive disorder in S. Korea. However, flexibility exercise did not have significant influence on health-related QOL in men with depressive disorder in S. Korea. Based on the results, in conclusion, the strength exercise and walking were effective exercise types to increase levels of health-related QOL in men with depressive disorder in S. Korea.